Functional dimorphism of leg extensors force-time characteristics in high trained Serbian male fencers - Milic, M. (Serbian Journal of Sports Sciences, 2015)
The aim of this study was to define functional dimorphism of leg extensors of Serbian elite fencers and to define models of different indicators to asses` isometric force - time characteristics of leg extensors, measured on 100ms, 180ms and 250ms from the beginning of the muscle contraction. The sample consisted of twelve Serbian male fencers, who were at international level but without high results. In order to assess the characteristics of the F - t isometric leg extensor force, high sensitive tensiometric probes and the standardized "leg press" test were used. Measuring range was defined upon 30 variables which representing contractile characteristics of leg extensors isometric force, measured in unilateral (dominant leg - RFDDO and no dominant leg - RFDND) and bilateral regime of muscle contraction. The results of Student T-test showed differences at statistical significant level in favor of the dominant leg for the following variables: F180ms t=2.272, p=0.044; F250ms t=2.487, p=0.030; RFD50% t=2.520, p=0.028; RFD180ms t=2.293, p=0.043; RFD250ms t=2.622, p=0.024. It was shown that specificity of fencing sport caused significant differences of F-t and RFD characteristics between dominant and no dominant leg extensors, especially in time interval between 180 and 250ms, which represent exact time during most of the fencing actions can be executed. However, those results are in some point contradictory with results of some previous studies. Because of that fact, it would be advisable to take the results of the present study as a starting point for a future similar research. Also, it would be advisable in a future thoroughly investigate the effects of long-term efforts of fencers training on the natural level of functional and sexual dimorphism of different age categories.